QBism : the future of quantum physics - Von Baeyer, Hans Christian; Von Baeyer, Lili (Cambridge, Massachusetts : Harvard University Press, 2016)
Measured by the accuracy of its predictions and the scope of its technological applications, quantum mechanics is arguably the most successful theory in science. Ironically, it is also one of the least well understood. Here the conventional view of quantum mechanics is outlined in simple, non-mathematical language, with emphasis on its most puzzling features. The key to understanding is probability, a common, everyday concept that turns out to be surprisingly problematic. Until 2002 all of the alternative interpretations of quantum mechanics relied on the modern, orthodox definition of probability that is taught in high school. Then a trio of theoretical physicists in USA and Britain suggested reverting to an older definition, called Bayesian probability and used routinely in other fields of science. Thus Quantum Bayesianism, abbreviated QBism, was born. According to QBism, probabilities are personal and subjective -- degrees of belief rather than objectively verifiable facts. QBism, for all its unconventionality, dissolves most of the weirdness of quantum mechanics even as it opens a window on a more personally engaging, more appealing and humane view of the universe.--
Introduction -- I. Quantum mechanics -- How the quantum was born -- Particles of light -- Wave/particle duality -- The wavefunction -- "The most beautiful experiment in physics" -- Then a miracle occurs -- Quantum uncertainty -- The simplest wavefunction -- II. Probability -- Troubles with probability -- Probability according to the Reverend Bayes -- III. Quantum Bayesianism -- QBism made explicit -- QBism saves Schrödinger's cat -- The roots of QBism -- Quantum weirdness in the laboratory -- All physics is local -- Belief and certainty -- IV. The QBist worldview -- Physics and human experience -- Nature's laws -- The rock kicks back -- The problem of the now -- A perfect map? -- The road ahead -- Appendix: four older interpretations of quantum mechanics.
Includes bibliographical references (pages 241-245) and index.
Print version record.
Keywords: Quantum Bayesianism; Quantum theory; SCIENCE -- Energy; SCIENCE -- Mechanics -- General; SCIENCE -- Physics -- General; Quantum Bayesianism; Quantum theory; Electronic books; Electronic books